Private Label Imitation of a National Brand: Implications for Consumer Choice and Law. (December 2014) - Aribarg, Anocha; Arora, Neeraj; Henderson, Ty; Kim, Youngju
In brand imitation lawsuits, the primary focus is on demonstrating harm as it relates to brand confusion. The authors' premise is that such a narrow focus does not capture the complete impact of brand imitation. They offer a broader, theory-based perspective of harm by proposing that brand imitation affects both brand consideration and preference in the consumer choice process. The authors establish a formal nexus between brand consideration and the legal doctrine "initial interest confusion." Using choice experiments and statistical modeling, they show that brand imitation harms the imitated brand even after controlling for brand confusion. Moreover, brand imitation harms not only the imitated brand but also other national brands in the category that are not being imitated. To quantify brand consideration and preference harm in financial terms, the authors propose two metrics: choice share shift and share-equalizing price cut. The results show that brand imitation harms the national brand more when the imitating brand is not associated with a well-known retailer and that brand imitation harm extends beyond brand confusion. The proposed framework provides both legal and managerial guidance.